The role of medicines and therapeutics committees structure in supporting optimal antibacterial use in hospitals in Uganda: A mixed method study - Kimbowa, Isaac Magulu; Ocan, Moses; Mukonzo, Jackson; Nakafeero, Mary; Eriksen, Jaran; Lundborg, Cecilia Stålsby; Ogwal-Okeng, Jasper; Obua, Celestino; Kalyango, Joan (Plos one, 2024)
Although the roles of Medicines and therapeutic committees (MTCs) have been expanding, there is limited information on the role of their structure in optimal antibacterial use in hospitals, especially in low-and-middle-income countries. Our study explored the structure and role of MTC in supporting antibacterial use in regional referral, general hospitals and tertiary private not-for-profit (PNFP) hospitals in Uganda. We conducted an explanatory sequential mixed-method approach with triangulation to explore the structure and functional role of MTCs from August 2019 to February 2020 in hospitals in Uganda. Quantitative data was collected using an interviewer-administered questionnaire among chairpersons or secretaries of MTCs and was analysed using descriptive statistics. We conducted key informant interviews using an interview guide among long-term serving members of MTCs to collect qualitative data which triangulated the quantitative data. The study revealed that sixteen hospitals had successfully established MTCs with an average duration of the MTCs’ existence of 5.6 (+2.7) years. The membership of the MTCs varied between 7 and 14, with a median value of 10, and the majority of members in MTCs were pharmacists (15 out of 16) and clinical specialists (13 out of 16). The most frequent subcommittees of the 16 hospitals MTC were supply chain (n = 14), antimicrobial stewardship (n = 13), and infection control (n = 12). Majority (14 out of 16) of the MTCs supported availability and access of antibacterial use by selecting and evaluating antibacterials agents for their formulary lists using established criteria. Additionally, 15 out 16 MTCs conducted antimicrobial stewardship activities to support optimal antimicrobial use. In our study, MTC membership and subcommittees were critical structural components that aided the selection and evaluation antibacterials on hospital formulary lists and they supported optimal antibacterial use through implementing various antimicrobial stewardship activities. There is a need for the Ministry of Health to conduct more training on operationalising MTCs structures in all hospitals.
Keywords: Medicines and therapeutic committees (MTCs); Hospitals; Uganda; Antibacterial use